THE EFFECTIVENESS OF POLICE GOES TO SCHOOL EDUCATION PROGRAM IN NUSA TENGGARA BARAT PROVINCE - Ratih Ayu Apsari (Journal of Indonesia Road Safety, 2020)
The present study aimed to evaluate the effectivity of the Police Goes to School in order to enhance students’ road safety. The research was conducted in Nusa Tenggara Barat (NTB) province with population is the Region Police of NTB with ten resort police stations. The chosen sample was Resort Police in Mataram and Lombok Barat. We also gathered the data from the schools in the work area of the resort polices with criteria of junior and senior high schools experienced and has no experience related to the Police Goes to School program. The total participants were 340 people consist of 320 students, 16 schools’ officers and 4 polices. The instrument employed in the study was interview sheet for police and school’s officers and questionnaire for the students. The data were analyzed using descriptive qualitative and quantitative methods. From the analysis, it was found that the traffic accident rate in the students’ age range decreased. Furthermore, the students and school’s office view that the program brings a lot of benefits and important to be continued. Tujuan penelitian ini adalah untuk mengevaluasi keefektivan program edukasi Polisi Masuk Sekolah dalam meningkatkan keselamatan berlalu lintas di kalangan pelajar. Lokasi penelitian adalah di Provinsi Nusa Tenggara Barat (NTB) dengan populasi penelitian adalah Polda NTB yang terdiri atas 10 Polres. Sample yang diambil adalah Polres Mataram dan Polres Lombok Barat. Selain itu, dilakukan penelitian ke sekolah dengan kriteria SMP dan SMA yang pernah dan belum pernah mendapat program edukasi Polisi Masuk Sekolah. Total partisipan yang terlibat dalam penelitian ini adalah 340 orang yang terdiri atas 320 siswa, 16 pengelola sekolah dan 4 orang polisi. Instrumen yang digunakan adalah lembar wawancara untuk polisi dan pengelola sekolah dan angket untuk siswa. Data yang diperoleh dianalisis dengan deskriptif kuantitatif dan kualitatif. Dari hasil penelitian diketahui diketahui terjadi penurunan angka kecelakaan lalu lintas di usia pelajar. Selain itu siswa dan petugas sekolah menilai kegiatan ini bermanfaat dan penting untuk dilanjutkan.